2019
DOI: 10.1039/c8cc09140d
|View full text |Cite
|
Sign up to set email alerts
|

Shell thickness controlled core–shell Fe3O4@CoO nanocrystals as efficient bifunctional catalysts for the oxygen reduction and evolution reactions

Abstract: Core–shell Fe3O4@CoO NCs have been demonstrated to be efficient catalysts for ORR and OER. The specific core/shell interaction can be ascribed to the main reason leading to their high catalytic performance. The shell thickness has a great influence on the catalytic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…54 It has been reported that cobalt oxide plays a positive role in ORR catalysis. 55,56 Dai et al reported a material consisting of Co 3 O 4 embedded in a carbon matrix, showing an E 1/2 of 0.83 V in 0.1 M KOH, which is attributed to the coupling effect by Co 3 O 4 and graphene. 50 Therefore, the formed intermediate cobalt oxide due to the transition from Co 9 S 8 also contributes to the high ORR catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 It has been reported that cobalt oxide plays a positive role in ORR catalysis. 55,56 Dai et al reported a material consisting of Co 3 O 4 embedded in a carbon matrix, showing an E 1/2 of 0.83 V in 0.1 M KOH, which is attributed to the coupling effect by Co 3 O 4 and graphene. 50 Therefore, the formed intermediate cobalt oxide due to the transition from Co 9 S 8 also contributes to the high ORR catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…54 It has been reported that cobalt oxide plays a positive role in ORR catalysis. 55,56 In addition to the superior activity, the anti-poisoning capability of the catalysts is also one of the most crucial factors for the long-term application of fuel cells because the impurities in air (including CO To the best of our knowledge, the strong resistance of CoS xbased catalysts towards S species has rarely been investigated in previous literature. Thus, the as-synthesized Co 9 S 8 /CoNSC exhibits superior electrocatalytic performance with strong resistance to poison, making it a promising catalyst for practical application in fuel cells.…”
Section: Electrochemical Performance Of the Orrmentioning
confidence: 99%
“…Through these efforts, a large number of transition metal‐based OER electrocatalysts with improved activity have been explored. However, to the best of our knowledge, most of the reported nonprecious electrocatalysts still need overpotentials larger than 200 mV to reach 10 mA cm −2 , leaving substantial room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, magnetically recoverable nanoparticles supported catalysts showed better catalytic activity than many traditional catalysts in organic synthesis [52–58] . It's a promising way to catalyze one‐pot tandem reaction with magnetic nanoparticles supported bifunctional catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[50] In addition, magnetically recoverable nanoparticles supported catalysts showed better catalytic activity than many traditional catalysts in organic synthesis. [52][53][54][55][56][57][58] It's a promising way to catalyze one-pot tandem reaction with magnetic nanoparticles supported bifunctional catalysts. Recently, we designed and synthesized a magnetic nanoparticles supported amine-palladium bifunctionalized catalyst NHÀ Pd(0)@MNP (Figure 1.…”
Section: Introductionmentioning
confidence: 99%